Zooplankton biomass dynamics in oligotrophic versus eutrophic conditions: a test of the PEG model. (16th October 2014) - Straile, Dietmar
Summary The model of the International Society of Limnology (SIL) Plankton Ecology working group (hereafter the PEG model) is a verbal model describing the patterns and driving factors of seasonal phytoplankton and zooplankton succession in oligotrophic and eutrophic lakes (Sommer et al., 1986). Despite being a citation classic, tests of the PEG model with respect to differences in zooplankton biomass dynamics between oligotrophic and eutrophic lakes are lacking. Here, I use the long‐term data from Lake Constance, which during the last 100 year changed from an (ultra‐) oligotrophic lake to a eutrophic lake and back to an oligotrophic lake to analyse trophic status differences in zooplankton biomass seasonality. Using data from one lake allows one to study trophic influences on biomass dynamics without the confounding effects of lake geographical setting and lake morphology, which complicate comparative dynamics in eutrophic versus oligotrophic lakes. However, environmental changes due to other driving factors, for example climate change, may possibly alter biomass dynamics as well. Data from Lake Constance do not support the differences in zooplankton seasonality in respect to peak timing between eutrophic and oligotrophic lakes suggested by the PEG model. Rather total zooplankton biomass, as well as cladoceran and copepod biomass showed a peak in May/June during all trophic conditions. Biomass dynamics of cladocerans during spring were more strongly influenced by water temperature than by trophic state. Furthermore, analyses of the geographical setting of the lakes considered in Sommer et al. (1986) suggest that the proposed differences in zooplankton seasonality between eutrophic and oligotrophic lakes are at least partially due to the confounding effect of lake altitudinal setting; the oligotrophic lakes were located at higher altitude than the eutrophic lakes. As a consequence of the results from Lake Constance, and the bias detected in the Sommer et al. (1986) study, a modified PEG model is proposed which considers low water temperature and not food limitation as the most important factor reducing zooplankton growth rate during early spring in both oligotrophic and eutrophic lakes.